The Effectiveness of STEM-PBL Learning Innovation in Climate Awareness Material to Improve Critical Thinking and Sustainability Consciousness of High School Students: Literature Review - Nurita Apridiana Lestari; Rosyidatul Mufida; Daniya Nabila Bayuputri; Muhammad Nur Hudha (JURNAL PENELITIAN PENDIDIKAN MATEMATIKA DAN SAINS, 2025)
The climate crisis demands that secondary education systems not only improve factual knowledge, but also foster awareness and sustainable action among students. One relevant approach is Science, Technology, Engineering, and Mathematics Problem Based Learning (STEM-PBL), which integrates contextual problem solving, collaboration, and evidence-based inquiry. This article aims to examine the trends and effectiveness of STEM-PBL implementation in climate awareness material in high schools, with a focus on improving critical thinking skills and sustainability consciousness. The research uses the Systematic Literature Review (SLR) method with a narrative approach, following the PRISMA 2020 guidelines. Articles were obtained through a Google Scholar search for the period 2020–2025 with the criteria of STEM-PBL intervention in climate awareness material in high schools and the use of critical thinking and sustainability consciousness measurement instruments. Of the 100 initial articles, 46 passed the eligibility stage, and after quality assessment, 10 articles were selected for synthesis. The results of the study show that STEM-PBL consistently improves high school students' data-based analysis, evaluation, inference, and argumentation skills. In addition, sustainability awareness increases through students' authentic experiences in investigating local climate issues, designing engineering solutions, and reflecting on the socio-environmental impacts of their choices. Several studies confirm that critical thinking serves as a cognitive link that translates scientific understanding into sustainable values and actions. The conclusion of this study is that the integration of STEM-PBL not only strengthens 21st-century competencies through critical thinking but also shapes pro-environmental dispositions that support the achievement of the SDGs, particularly goal 13. Limitations identified include limited sample coverage, heterogeneity of designs, and the use of non-standardized instruments, making further longitudinal and cross-context research essential. Keywords: STEM-PBL, critical thinking, sustainability consciousness, climate awareness.